Investigating the mainstreaming of inclusive education in Teacher Education Practice for Pedagogical Proficiency through Education for Sustainable Development Change Projects in Southern Africa - Souza, Ben (Rhodes University, Faculty of Education, Department of Secondary and Post School Education)
Globally, there are policy and practice efforts to mainstream inclusive education in different sub-fields of education. Part of the efforts have focused on investigating and finding practical mechanisms for the mainstreaming process in teacher education. Anecdotally, Education for Sustainable Development (ESD), with its focus on transformative education, collaborative learning, the community of practice and the whole institution approach, has the potential to mainstream inclusive education in teacher education practices if grounded in sociocultural realities rather than mere ideological framing. This situation is related to the need for more transformative capabilities for teacher educators to prepare teachers for inclusive pedagogical proficiency. However, in a southern African context, the outlook of the potential of pedagogical proficiency from the nexus of inclusive education, ESD and teacher education is disjointed. As such, this study focused on investigating the mainstreaming of inclusive education in teacher education practice for pedagogical proficiency through ESD Change Projects in Southern Africa, examining cases from Malawi, Tanzania and Eswatini. The study intended to gain an understanding of inclusive education and ESD in these countries, identify areas for strengthening inclusive education in teacher education practice, collaborate with teacher educators to develop strategies for mainstreaming inclusive education, and generate indicators for monitoring and evaluating inclusive education in teacher education contexts. The study used Urie Bronfenbrenner's bioecological theory of human development and Lev Vygotsky's sociocultural theory of learning as theoretical and analytical frameworks. The study also employed Roy Bhaskar's critical realism philosophy as an underlabourer or a meta-theoretical framework. The study further adapted the Vygotsky-informed Engestrom's expansive learning as a methodological torch. Together, these frameworks were used to analyse selected Change Projects within Sustainability Starts with Teachers (SST) programme, which focused on ESD capacity building in teacher educators from 11 southern African countries. In this regard, the research utilised a qualitative nested case study design. A formative interventionist research approach supported the cases in Malawi, Tanzania and Eswatini, with the study selecting SST Change Projects dealing with inclusive education through an initial scoping questionnaire. Data were generated through 12 in-depth interviews, nine workshops (involving 24 participants), document reviews, observations and reflective journals. Thematic ii analysis, employing a critical realist approach with abductive and retroductive reasoning, guided the reflexive presentation and discussion of research findings. The research findings revealed a common understanding of inclusive education as providing equal educational opportunities, ESD as supporting sustainable development, and teacher education as skill development. The research findings also highlighted the influence of teacher educators' biopsychosocial characteristics on their perceptions of inclusive education, ESD and teacher education. Areas requiring improvement in teacher education systems included resources, attitude change, financing, cooperation, collaboration and leadership. Strategies for mainstreaming inclusive education in teacher education practice for pedagogical proficiency included curriculum implementation, policy shift, contextualisation and interactive systems. Monitoring and evaluation in all three cases focused on teaching practice, assessment, feedback tools, forums and curriculum implementation, but the absence of specific indicators for monitoring and evaluation was evident. These findings suggest multi-layered and complex implications for policy formulation, implementation practices and future research. Therefore, this thesis argues that, in a southern Africa context, the potential of pedagogical proficiency from the nexus of inclusive education, ESD and teacher education involves considering biopsychosocial characteristics to facilitate the capabilities of teacher educators. This situation necessitates utilising inclusivity mechanisms in pre-service teacher training grounded in biosocial and psychocultural realities of the region's educational challenges. Consequently, this thesis proffers the Sustainable Inclusive Pedagogical Proficiency Process (SIP3) model as a framework to actualise the nexus of inclusive education, ESD and teacher education, and bring into focus its pedagogical proficiency potential which eventually helps with the mainstreaming process in teacher education practice via ESD. The study reported in this thesis contributes to international theory and practice development for inclusivity and ESD in teacher education practice, provides indicators for monitoring inclusive quality education in teacher education practice, and introduces a contextual dynamics model for comparative education research. The thesis is structured in eight chapters, introducing the study context, addressing literature gaps, presenting the theoretical framework, detailing research design, exploring specific cases in Malawi, Tanzania and Eswatini, discussing the research findings and its implications, and concluding with recommendations for change and future research.
Keywords: Inclusive education -- South Africa; Education for sustainable development; Teachers Training of -- South Africa; Teacher effectiveness; Critical realism; Social learning; Bioecological model